Surgical natural uveoscleral outflow activation and phacoemulsification with intraocular lens implantation in the combined treatment of patients with glaucoma and cataract combination - N. G. Zavgorodnaya; T. P. Gaidarzhi (Zaporožskij Medicinskij Žurnal)
Aim. Surgery of glaucoma in combination with cataract is an important modern ophthalmology issue. Combination of the diseases can be met in 17-76 % patients.